Rozwiązane

rozwiaz rownanie
-x²+6x+1 =0
6x²-2x-1 =0



Odpowiedź :

RAWЯ

Odpowiedź w załączniku. Pozdrawiam.

Zobacz obrazek RAWЯ

Odpowiedź:

[tex]-x^{2} +6x+1=0[/tex]

Δ = [tex]6^{2} +4[/tex] = [tex]40[/tex]

[tex]x_{1} =\frac{-6-2\sqrt{10} }{-2} =3+\sqrt{10}[/tex]

[tex]x_{2} =\frac{-6+2\sqrt{10} }{-2} =3-\sqrt{10}[/tex]

[tex]6x^{2} -2x-1=0[/tex]

Δ = [tex](-2)^{2} +4*6=28[/tex]

[tex]x_{1} = \frac{2-2\sqrt{7}}{12} = \frac{1-\sqrt{7}}{6}[/tex]

[tex]x_{2} =\frac{2+2\sqrt{7} }{12} =\frac{1+\sqrt{7} }{6}[/tex]      

Szczegółowe wyjaśnienie: